A passive-flow microfluidic device for imaging latent HIV activation dynamics in single T cells1. Issue 9 (1st September 2015) - Ramji, Ramesh; Wong, Victor C.; Chavali, Arvind K.; Gearhart, Larisa M.; Miller-Jensen, Kathryn
<x xml:space="preserve">Abstract</x> We designed a passive-flow microfluidic device to image HIV activation dynamics in live individual T cells. We show that drugs that activate transcription factors stimulate latent HIV with distinct noise profiles from drugs that inhibit chromatin remodeling proteins.